Associations between pain severity and physical, psychosocial, and health literacy-related factors in shoulder pathologies - Mehmet Canlı; İrem Canlı; Hikmet Kocaman; Şafak Kuzu; Anıl Özüdoğru; Yusuf Topal; Özlem Yamanyurt; Kübra Şahin; Neziha Nur Tanrıverdi; Nadire Sultan Dolma (Turkish Journal of Kinesiology, 2026)
This study aimed to examine the associations between pain severity and physical, psychosocial, and health literacy-related factors in individuals with shoulder pathologies. Seventy individuals with physician-diagnosed shoulder pathologies were included in this cross-sectional study. Pain severity was assessed using the Visual Analog Scale at rest, during activity, and at night. Hand grip strength, kinesiophobia, upper extremity disability, health-related quality of life, digital health literacy, and perceived exercise benefits/barriers were evaluated using validated tools. Pearson correlation analysis was used to examine the relationships between pain scores and clinical variables. Pain severity was negatively correlated with hand grip strength, health-related quality of life, digital health literacy, and exercise-related perceptions, and positively correlated with upper extremity disability and kinesiophobia scores. Rest pain showed the strongest correlation with hand grip strength (r=-0.754), followed by upper extremity disability (r=0.690) and physical quality of life (r=-0.677). Activity pain was moderately associated with hand grip strength (r=-0.659), upper extremity disability (r=0.526), and exercise-related perceptions (r=-0.501). Night pain demonstrated the strongest associations with hand grip strength (r=-0.773), physical quality of life (r=-0.730), and upper extremity disability (r=0.718) (all p